Built to win : - Movius, Hallam (Harvard Business Press, 2009)
In Built to Win, authors Susskind and Movius argue that negotiation must be a strategic core competency. Drawing on their decades of training and consulting work, as well as a robust theory of negotiation, the authors provide a step-by-step model for building organizational competence. They show why the approach of ?training and more training? is a weak strategy. The authors also describe the organizational barriers that so often plague even experienced negotiators, and recommend ways of overcoming them. Built to Win explains the crucial role that leaders must play in setting goals, aligning incentives, pinpointing metrics, and supporting learning platforms to promote long-term success. A final chapter provides practical ?how-to? tools to help you start your own organizational improvement process.